2019
DOI: 10.1186/s12872-019-1191-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of circular RNAs and environmental risk factors with coronary heart disease

Abstract: Background Coronary heart disease (CHD) is a complex disease caused by multi-factors and a major threat to human health. Circular RNAs (circRNAs) have critical roles in various biological processes and diseases. This study explores the independent role of circRNAs and their interaction with environmental factors in CHD. Methods A case–control study was conducted from March 2015 to September 2017 in Fuzhou, China. A total of 585 CHD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 30 publications
(25 reference statements)
1
8
0
Order By: Relevance
“…greatly reduce the risk of complications arising from CHD, side-effects can greatly reduce quality of life (33). Evidence has shown that environmental factors, genomes, and epigenetics play crucial roles in it etiology (27). In this study, we confirmed that the elevated expression of lnc-MICALL2-2 is an independent risk factor for CHD after adjustment for environmental factors, and knockdown subsequently confers protection against early pathological processes of oxLDL-induced CHD.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…greatly reduce the risk of complications arising from CHD, side-effects can greatly reduce quality of life (33). Evidence has shown that environmental factors, genomes, and epigenetics play crucial roles in it etiology (27). In this study, we confirmed that the elevated expression of lnc-MICALL2-2 is an independent risk factor for CHD after adjustment for environmental factors, and knockdown subsequently confers protection against early pathological processes of oxLDL-induced CHD.…”
Section: Discussionsupporting
confidence: 73%
“…LncRNA expression levels were calculated using the 2 − CT method. Supplementary Table 2 lists the primers used for qRT-PCR, similar research methods have been applied in previous studies (27,28).…”
Section: Quantitative Real-time Polymerase Chain Reaction (Qrt-pcr)mentioning
confidence: 99%
“…Second, circRNAs are also highly expressed in the heart [89] and are reported to play a role in cardiac remodeling [90], stress response [91], endothelial-to-mesenchymal transition [92], metabolism [93,94], immune tolerance [95], atrial fibrillation [96], and apoptosis [97]. Thus, these circRNAs are suggested to participate in heart diseases such as heart failure [91,97,98], ventricular septal defect [99], chronic heart disease [92,[100][101][102], alcoholic cardiomyopathy [93], and rheumatic heart disease [96]. In the lung, circRNAs have been found to be important in lung fibrosis [103], cell growth [104], cell migration and invasion [105][106][107][108], cancer tumorigenesis [109], and so on; thus, these circRNAs play a role in various lung-related diseases such as lung cancer [105,107,[110][111][112], lung injury [113], and pulmonary hypertension [114].…”
Section: Major Biological Function and Disease Relevancementioning
confidence: 99%
“…Research about circRNAs as potential biomarker for CAD is constantly developing ( Table 2 ). A recent microarray study identified 3423 dysregulated circRNAs in five CAD patients and five matched healthy controls [ 48 ]. The expression levels of hsa_circ_0001946, hsa_circ_0008507 and hsa_circ_0000284 were significantly elevated in peripheral CAD blood leukocytes, consistent with their expressions in the peripheral blood, but exhibited significant differences in various populations.…”
Section: Circrna Serves As Biomarkers In Scd-related Diseasesmentioning
confidence: 99%